GABA and Glutamate - New Developments in Neurotransmission Research 2018
DOI: 10.5772/intechopen.72678
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists of Ionotropic Receptors for the Inhibitory Neurotransmitter GABA: Therapeutic Indications

Abstract: Agents that antagonize the action of GABA on ionotropic receptors are widely used to probe the function of this neurotransmiter. Three such agents are in common use: bicuculline, gabazine, and picrotoxinin. These three agents produce convulsions on systemic administration but act in signiicantly diferent ways. Bicuculline is a competitive antagonist of GABA A receptors. Gabazine is also a competitive antagonist of GABA A receptors, interacting with diferent residues on the receptors. Picrotoxinin is a noncompe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that pharmacological targeting of GABA A Rs can alleviate neuropathic pain in a peripheral nerve injury model 19 , yet no evidence has been provided regarding the role of any GABA A R subunit on hindlimb functional recovery in SCI rats. We first applied sustained administration of bicuculline, a competitive antagonist of GABA A Rs 20 , either with or without hUC-MSC transplantation to assess the effects of GABA A Rs on hUC-MSC-mediated SCI repair. IF staining showed that the general expression levels and/or distributions of different GABA A R subunits were not obviously affected by bicuculline treatment at the epicenter (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that pharmacological targeting of GABA A Rs can alleviate neuropathic pain in a peripheral nerve injury model 19 , yet no evidence has been provided regarding the role of any GABA A R subunit on hindlimb functional recovery in SCI rats. We first applied sustained administration of bicuculline, a competitive antagonist of GABA A Rs 20 , either with or without hUC-MSC transplantation to assess the effects of GABA A Rs on hUC-MSC-mediated SCI repair. IF staining showed that the general expression levels and/or distributions of different GABA A R subunits were not obviously affected by bicuculline treatment at the epicenter (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of both gabazine and picrotoxin treatment at ambient CO 2 on specific behavioural traits in the current study suggests that receptors in I. pygmaeus are sensitive to gabazine and picrotoxin. Furthermore, the concentrations used did not cause any obvious convulsions, which can be produced by the excitotoxic effects of GABA A R antagonists when administered systemically (Hinton and Johnston, 2018). The concentrations used are based on previous in vivo studies showing behavioural change with no convulsant effects reported (Biscocho et al, 2018;Chivers et al, 2014;Hamilton et al, 2013;Nilsson et al, 2012;Rittschof et al, 1986;Watson et al, 2014).…”
Section: Behavioural Effects Of Gabazine and Picrotoxinmentioning
confidence: 99%
“…19 Since systemic administration of brain-permeant unspecific or subtype-unselective GABA A R antagonists (i.e., PTX or BCC) causes profound convulsant effects, they have been used as powerful tools to elucidate the physiological importance of the receptors without any therapeutic potential. 20 Indeed, although a number of GABA A R agonists or PAMs are approved for clinical use, the silent allosteric modulator flumazenil is the only GABA A R antagonist currently used in medical practice. 21 Due to the low number of GABA A R subtype-specific antagonists, the potential of such compounds as CNS targeting therapeutics has only been sparingly studied.…”
Section: ■ Introductionmentioning
confidence: 99%